Nutraceutical Targeting of Inflammation-Modulating microRNAs in Severe Forms of COVID-19: A Novel Approach to Prevent the Cytokine Storm - Desjarlais, Michel; Wirth, Maëlle; Lahaie, Isabelle; Ruknudin, Pakiza; Hardy, Pierre; Rivard, Alain; Chemtob, Sylvain (Frontiers in Pharmacology, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has become the number one health problem worldwide. As of August 2020, it has affected more than 18 million humans and caused over 700,000 deaths worldwide. COVID-19 is an infectious disease that can lead to severe acute respiratory syndrome. Under certain circumstances, the viral infection leads to excessive and uncontrolled inflammatory response, which is associated with the massive release of inflammatory cytokines in pulmonary alveolar structures. This phenomenon has been referred to as the ‘cytokine storm’, and it is closely linked to lung injury, acute respiratory syndrome and mortality. Unfortunately, there is currently no vaccine available to prevent the infection, and no effective treatment is available to reduce the mortality associated with the severe form of the disease. The cytokine storm associate with COVID-19 shows similarities with those observed in other pathologies such as sepsis, acute respiratory distress syndrome (ARDS), acute lung injury (ALI) and other viral infection including severe cases of influenza. However, the specific mechanisms that cause and modulate the cytokine storm in the different conditions remain to be determined. micro-RNAs (miRs) are important regulators of gene expression, including key inflammatory cytokines involved in the massive recruitment of immune cells to the lungs such as IL1, IL6, and TNF. In recent years, it has been shown that nutraceutical agents can modulate the expression of miRs involved in the regulation of cytokines in various inflammatory diseases. Here we review the potential role of inflammatory-regulating-miRs in the cytokine storm associated with COVID-19, and propose that nutraceutical agents could represent an alternative therapeutic approach to modulate dysregulated miRs in this condition and provide effective benefits in severe respiratory distress.